2019
DOI: 10.1530/erc-18-0582
|View full text |Cite
|
Sign up to set email alerts
|

Gastric neuroendocrine neoplasias: manifestations and comparative outcomes

Abstract: Although gastric neuroendocrine neoplasias (gNEN) are an orphan disease, their incidence is rising. The heterogeneous clinical course powers the ongoing discussion of the most appropriate classification system and management. Prognostic relevance of proposed classifications was retrospectively analysed in 142 patients from a single tertiary referral centre. Baseline, management and survival data were acquired for statistical analyses. The distribution according to the clinicopathological typification was gNEN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In the stomach NENs can present as multifocal subepithelial lesions. These are usually diagnosed by standard mucosal biopsy techniques [12]. There is a stark contrast between the usually aggressive nature of esophageal NENs (often high grade small-cell type in nature) and the mostly more indolent nature of gastric NENs, so that NENs from each GI site warrant separate discussion (▶ Table 2).…”
Section: Nensmentioning
confidence: 99%
“…In the stomach NENs can present as multifocal subepithelial lesions. These are usually diagnosed by standard mucosal biopsy techniques [12]. There is a stark contrast between the usually aggressive nature of esophageal NENs (often high grade small-cell type in nature) and the mostly more indolent nature of gastric NENs, so that NENs from each GI site warrant separate discussion (▶ Table 2).…”
Section: Nensmentioning
confidence: 99%
“…Some scholars have found that the postoperative survival time of gastric cancer patients with neuroendocrine differentiation (NED) is shorter than that of patients without NED, and the difference is statistically significant. This might imply that neuroendocrine differentiation plays a role in promoting gastric cancer progression [ 12 , 13 ]. Some scholars believe that the survival time of tumor patients with high expression of neuroendocrine markers CgA and Syn is significantly lower than that of patients with low expression.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric atrophy associated with chronic H . pylori ‐infection may also be a factor in some cases 19–21 . Both type 1 and type 2 gNEN typically arise as multiple gastric polyps (See Case Study 1 and Figure 1) or subepithelial lesions (SEL), type 2 being quite rare while type 1 is by far the most frequent gNEN 16–18 …”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Gastric atrophy associated with chronic H. pylori-infection may also be a factor in some cases. [19][20][21] Both type 1 and type 2 gNEN typically arise as multiple gastric polyps (See Case Study 1 and Figure 1) or Tumor is also known in the literature as small cell carcinoma of the oesophagus.…”
Section: Gastric Neuroendocrine Neoplasiamentioning
confidence: 99%